The secreted Nimrod protein NimB1 negatively regulates early steps of apoptotic cell phagocytosis in Drosophila. - Dolgikh, A.; Rommelaere, S.; Ghanem, A.; Petrignani, B.; Poidevin, M.; Kurant, E.; Lemaitre, B. (Development, 2025)
Efferocytosis, the efficient clearance of apoptotic cells (ACs) by phagocytes, is vital for maintaining tissue homeostasis. Here, we reveal the role of the secreted protein NimB1 in reducing apoptotic cell recognition and binding in the early stages of efferocytosis. NimB1 is expressed in macrophages (also called plasmatocytes) and binds to ACs in a phosphatidylserine-dependent manner. Structural analysis shows that NimB1 shares striking similarities with the bridging molecule NimB4, and possesses two phosphatidylserine-binding motifs, supporting its role in efferocytosis. Larval macrophages of NimB1-null Drosophila mutants display a hyper-phagocytic phenotype characterized by increased engulfment of ACs. Confocal imaging reveals that NimB1 specifically inhibits early steps in internalization of ACs, but does not impact phagosome maturation. We find that NimB1 is a secreted factor that negatively regulates efferocytosis, antagonizing the role of NimB4. Our study and the analogous opposing roles of Draper Isoforms II and I in efferocytosis suggest that a balance of negative and positive regulators allows optimization of the rate of apoptotic cell clearance by macrophages.